Collaboration : how leaders avoid the traps, create unity, and reap big results - Hansen, Morten T. (Boston, Mass. : Harvard Business Press, 2009)
Many leaders inherently know that in today's competitive environment, companywide collaboration is an imperative for successful strategy execution. Sadly, most cross-unit collaborative efforts end up wasting time, money, and resources. This book shows managers how to get it right through 'disciplined collaboration'. Deciding when to collaborate- and when not to- is the first critical step in disciplined collaboration. To master collaboration is to know when not to do it. Highlighted also are four common collaboration traps that managers must avoid: the 'not-invented-here' syndrome; hoarding; search problems; and transfer issues.
Getting collaboration wrong-- or getting it right -- Know when to collaborate, and when not to -- Spot the four barriers to collaboration -- Lever 1 : unify people -- Lever 2 : cultivate t-shaped management -- Lever 3 : build nimble networks -- Grow to be a collaborative leader.
Includes bibliographical references (pages 211-219) and index.
Description based on print version record.
Keywords: Industrial management; Industrial management -- Philosophy; Leadership; Teams in the workplace; Teams in the workplace -- Management; Führung; Kooperation; Führung; Kooperation; Industrial management; Industrial management -- Philosophy; Leadership; Teams in the workplace; Teams in the workplace -- Management; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; elektronické knihy; electronic books